Development of Aflatoxin B(1)-Lysine Adduct Monoclonal Antibody for Human Exposure Studies - Wang, Jia-Sheng (American Society for Microbiology, 2001)
Mouse monoclonal antibodies were developed against a synthetic aflatoxin B(1) (AFB)-lysine–cationized bovine serum albumin conjugate. The isotype of one of these antibodies, IIA4B3, has been classified as immunoglobulin G1(λ). The affinity and specificity of IIA4B3 were further characterized by a competitive radioimmunoassay. The affinities of IIA4B3 for AFB and its associated adducts and metabolites are ranked as follows: AFB-lysine > 8,9-dihydro-8-(2,6-diamino-4-oxo-3,4-dihydropyrimid-5-yl formamido)-9-hydroxy-AFB > AFB = 8,9-dihydro-8-(N(7)-guanyl)-9-hydroxy-AFB > aflatoxin M(1) > aflatoxin Q(1). IIA4B3 had about a 10-fold higher affinity for binding to AFB-lysine adduct than to AFB when (3)H-AFB–lysine was used as the tracer. The concentration for 50% inhibition for AFB-lysine was 0.610 pmol; that for AFB was 6.85 pmol. IIA4B3 had affinities at least sevenfold and twofold higher than those of 2B11, a previously developed antibody against parent AFB, for the major aflatoxin-DNA adducts 8,9-dihydro-8-(N(7)-guanyl)-9-hydroxy-AFB and 8,9-dihydro-8-(2,6-diamino-4-oxo-3,4-dihydropyrimid-5-yl formamido)-9-hydroxy-AFB, respectively. An analytical method based on a competitive radioimmunoassay with IIA4B3 and (3)H-AFB–lysine was validated with a limit of detection of 10 fmol of AFB-lysine adduct. The method has been applied to the measurement of AFB-albumin adduct levels in human serum samples collected from the residents of areas at high risk for liver cancer.